2011
DOI: 10.1371/journal.pone.0029043
|View full text |Cite
|
Sign up to set email alerts
|

A miR-200b/200c/429-Binding Site Polymorphism in the 3′ Untranslated Region of the AP-2α Gene Is Associated with Cisplatin Resistance

Abstract: The transcription factor AP-2α functions as a tumor suppressor by regulating various genes that are involved in cell proliferation and apoptosis. Chemotherapeutic drugs including cisplatin induce post-transcriptionally endogenous AP-2α, which contributes to chemosensitivity by enhancing therapy-induced apoptosis. microRNAs (miRNAs) miR-200b, miR-200c and miR-429 (miR-200b/200c/429) are up-regulated in endometrial and esophageal cancers, and their overexpression correlates with resistance to cisplatin treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 31 publications
(48 reference statements)
3
54
0
Order By: Relevance
“…Surprisingly, miRNAs also have the potential to suppress several target genes simultaneously (2). Similarly, numerous miRNAs play important roles as either oncogenes or tumor suppressor genes, and are involved in a variety of cellular processes including proliferation, apoptosis, tumorigenesis, and chemoresistance (3)(4)(5). Furthermore, several studies have shown that dysregulated miRNA expression is frequently found in various human cancers (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, miRNAs also have the potential to suppress several target genes simultaneously (2). Similarly, numerous miRNAs play important roles as either oncogenes or tumor suppressor genes, and are involved in a variety of cellular processes including proliferation, apoptosis, tumorigenesis, and chemoresistance (3)(4)(5). Furthermore, several studies have shown that dysregulated miRNA expression is frequently found in various human cancers (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers (Richardson et al, 2011) basing on the list of SNPs from GWAS, or in strong LD with a GWAS SNP performed a genome-wide scan of SNPs that abrogate or create miRNA recognition element (MRE) seed sites (MRESS) and identified high priority candidate SNPs for functional studies and for disease risk prediction. Other researchers (Wu et al, 2011) discovered the relationship between specific genes expression or miRNA level and diseases, so they thought that SNPs within miRNA target sites may influence their encoded target-mRNAs and their downstream effectors and they would predict the 3'UTR of these genes contains potential MREs and verify that these mutations maybe as a key in regulating gene expression. At present, all studies the on gene variation in miRNA-binding regions were performing several kinds of arithmetic or getting help from various websites.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of miR-200b, miR-200c and miR-429, which inhibit transcription factor AP-2α, is upregulated in endometrial cancer and the rate of expression is positively correlated with resistance to cisplatin. However, SNP (rs1045385A>C) decreases the effect on AP-2α, and sensitivity to cisplatin is increased (Wu et al, 2011). These studies suggest that a comprehensive investigation of which miRNA causes resistance or increases sensitivity to a particular drug will improve selection of drug treatment.…”
Section: Application Of Mirna For Treat-ment Of Endometrial Cancermentioning
confidence: 96%